Fibromodulin reprogrammed cells: A novel cell source for bone regeneration. (March 2016) - Li, Chen-Shuang; Yang, Pu; Ting, Kang; Aghaloo, Tara; Lee, Soonchul; Zhang, Yulong; Khalilinejad, Kambiz; Murphy, Maxwell C.; Pan, Hsin Chuan; Zhang, Xinli; Wu, Benjamin; Zhou, Yan-Heng; et al.
Abstract: Pluripotent or multipotent cell-based therapeutics are vital for skeletal reconstruction in non-healing critical-sized defects since the local endogenous progenitor cells are not often adequate to restore tissue continuity or function. However, currently available cell-based regenerative strategies are hindered by numerous obstacles including inadequate cell availability, painful and invasive cell-harvesting procedures, and tumorigenesis. Previously, we established a novel platform technology for inducing a quiescent stem cell-like stage using only a single extracellular proteoglycan, fibromodulin (FMOD), circumventing gene transduction. In this study, we further purified and significantly increased the reprogramming rate of the yield multipotent FMOD reprogrammed (FReP) cells. We also exposed the 'molecular blueprint' of FReP cell osteogenic differentiation by gene profiling. Radiographic analysis showed that implantation of FReP cells into a critical-sized SCID mouse calvarial defect, contributed to the robust osteogenic capability of FReP cells in a challenging clinically relevant traumatic scenario in vivo . The persistence, engraftment, and osteogenesis of transplanted FReP cells without tumorigenesis in vivo were confirmed by histological and immunohistochemical staining. Taken together, we have provided an extended potency, safety, and molecular profile of FReP cell-based bone regeneration. Therefore, FReP cells present a high potential for cellular and gene therapy products for bone regeneration.